STUDY OF LAND USE AND SEASON CHANGES ON WATER QUALITY IN THE HULU CITARUM RIVER WITH STATISTICAL AND SPATIAL APPROACH - Yusuf Habibbullah, Muhammad
River water management is an important part of the sustainability of natural resources, especially water. Therefore, it is necessary to analyze water quality data intensively from a spatial, temporal, and seasonal perspective to be able to understand and mitigate environmental impacts that occur in river water. This study aims to analyze spatial-temporal and seasonal trends in water quality in the Upper Citarum River in Indonesia and relate them to changes in land use over a period of time. Water quality data consisting of 20 parameters and Landsat image data for the period from 2011 to 2020 were compiled and analyzed. This study found that the parameters of TSS, phenol, BOD, COD, chlorine, sulfide, feacal coliform and total coliform did not meet water quality standards. The parameter concentrations of DHL, temperature, TDS, TSS, ammonia, detergent, phenol, total phosphate, BOD, COD, oils & fats, nitrate, nitrite, free chlorine, sulfide, fecal coliform, and total coliform have increased the trend from upstream to downstream from time to time. This study also found that the proportion of residential, industrial and other building land greatly affects the quality of the Upper Citarum River and is vulnerable to contributing to water pollution in the river. In addition, the analysis of the main components of water quality data shows that organic waste, industrial waste, surface water runoff, and domestic wastewater are the most important factors to describe the variability of total water quality in the Upper Citarum River. This study demonstrates the application of GIS-based multivariate analysis in water quality monitoring, which can be used by watershed stakeholders to develop data-driven interventions to improve river water quality